Influence of reaction conditions on the self‐assembly of the natural silk sericin protein. Issue 3 (9th April 2016) - Li, Wenhua; Su, Xiuping; Zhong, Qiwei; Liu, Zhaogang; Cai, Yurong; Yao, Juming
ABSTRACT: In the past years, the self‐assembly of specific proteins has been paid more and more attention due to their significant role in human health and fabrication of new materials. In this article, we explore the effect of reaction conditions on the self‐assembly of natural silk sericin protein, including the molecular weight and the concentration of sericin, pH, and metal ions in the reaction system. The results indicate that all these factors, especially species and concentration of metal ions, could influence the self‐assembly process of the silk sericin protein. A series of assemblies with various morphologies can be fabricated by modulating the reaction condition. The article may provide some clue for the understanding of the protein self‐assembly in the body and a method to fabricate new organic materials with different morphology. Microsc. Res. Tech. 80:298–304, 2017. © 2016 Wiley Periodicals, Inc.